Weakening the lower crust: conditions, reactions and deformation - Tacchetto, Tommaso; Clark, Chris; Erickson, Timmons; Reddy, Steven; Bhowany, K.; Hand, M. (2022)
The impact of fluid infiltration on the deformation mechanisms that facilitate the development of lower-crustal ductile shear zones is evaluated through a multiscale structural, geochemical, and thermobaric analysis undertaken across a shear zone/wall-rock interface exposed on the island of Radøy in the Bergen Arcs (western Norway). At the outcrop scale, the shear zone is characterized by a strain gradient reflected in the progressive evolution from weakly-deformed coronitic gabbroic anorthosite to finer-grained foliated amphibolite characterized by a distinct mineral lineation, shear bands, and σ-type porphyroblasts. Electron backscattered diffraction (EBSD) crystallographic orientation data from the coronitic gabbroic anorthosite define an initial stage of shear localization whereby most of the deformation is accommodated by crystal plasticity within plagioclase accompanied by grain size reduction through subgrain rotation recrystallization. As deformation proceeds, complementary to increasing fluid-rock interaction, the replacement of the anhydrous mineral assemblage results in strain partitioning and the development of a heterogeneous ductile shear zone. At the grain scale, the distinct CPO of amphibole, epidote and kyanite suggests deformation being dominated by crystal plastic mechanisms. U-Pb age data obtained from zircon grains within the Caledonian shear zone cluster at 883 ± 3 Ma consistent with ages derived from the granulite facies assemblage. Phase equilibria modelling indicates conditions of deformation within the shear zone at ~600 °C and ~11 kbar, consistent with mid-crustal levels at amphibolite facies conditions. Conversely, geochemical data from garnet of the shear zone characterized by the absence of Eu anomaly, point to mineralogical reactions having initially occurred at higher pressure conditions. This study highlights the key role of fluid infiltration and metamorphic reactions on strain localization processes which can facilitate the ductile deformation of the original assemblage and ultimately contribute to the rheological weakening of an anhydrous and refractory lower crust.